CONFLICT RESOLUTION METHODS: CASE STUDY AT THE FIDEL PEREYRA BILINGUAL EDUCATIONAL INSTITUTION, CUSCO 2021 - Muñoz Muñoz, Delia (2023)
In Peru, the State policy is bilingual intercultural education, especially in rural areas; its execution should solve the conflicts that according to the reports of the Ombudsman¨s Office and the Census Evaluational quality. The purpose of this research work is to describe the coincidences between the methods of conflict resolution and traditional Machiguenga justice in the Fidel Pereyra Cusco Bilingual Educational Institution, 2021. The previous one was carried out through a qualitative approach characterized by a study of a case carried out in the Machiguenga native community Nueva Luz. The results found to show a relationship in the use of mediation and conciliation of conflict resolution methods and the content of the statute and internal regulations of the community of Nueva Luz, for which our proposal is aimed at knowing traditional Machiguenga justice and contextualizing it. In the management instruments specifically in the internal regulations of the Fidel Pereyra Bilingual Educational Institution will allow us an orderly and supportive environment.